Crossing b(l)ack : mixed-race identity in modern American fiction and culture - Dagbovie-Mullins, Sika A. (University of Tennessee Press, 2013)
The past two decades have seen a growing influx of biracial discourse in fiction, memoir, and theory, and since the 2008 election of Barack Obama to the presidency, debates over whether America has entered a "post-racial" phase have set the media abuzz. In this penetrating and provocative study, the author adds a new dimension to this dialogue as she investigates the ways in which various mixed-race writers and public figures have redefined both "blackness" and "whiteness" by invoking multiple racial identities. Focusing on several key novels - Nella Larsen's Quicksand (1928), Lucinda Roy's Lady Moses (1998), and Danzy Senna's Caucasia (1998) - as well as memoirs by Obama, James McBride, and Rebecca Walker and the personae of singer Mariah Carey and actress Halle Berry, the author challenges conventional claims about biracial identification with a concept she calls "black-sentient mixed-race identity." Whereas some multiracial organizations can diminish blackness by, for example, championing the inclusion of multiple-race options on census forms and similar documents, a black-sentient consciousness stresses a perception rooted in blackness - "a connection to a black consciousness," writes the author, "that does not overdetermine but still plays a large role in one's racial identification." By examining the nuances of this concept through close readings of fiction, memoir, and the public images of mixed-race celebrities, this book demonstrates how a "black-sentient mixed-race identity reconciles the widening separation between black/white mixed race and blackness that has been encouraged by contemporary mixed-race politics and popular culture."